Media Pembelajaran E-Task dengan Metode Cooperative Learning Untuk Siswa SMA Negeri 3 Bukittinggi - Ningsih, Sri Restu; Putri, Yessy Prima; Lestari, Safia Putri (JOSTECH: Journal of Science and Technology, 2021)
This study aims to design a learning media application for assignment collection and delivery of material online using the Cooperative Learning method. Based on the results of the survey conducted, it was found that some students experienced difficulties in receiving lessons and also in collecting assignments if they were unable to attend school, so that teachers also had difficulty in recapitulating student scores because they had to work repeatedly. The system to be built is an e-task application, which is an application regarding web-based student assignments using the PHP programming language, and using the MYSQL database and the Cooperative Learning method based on visible facts. The research method uses the waterfall model with the Unified Modeling Language (UML) design tool. The results of the study are in the form of learning media applications that can facilitate the work of teachers and students in carrying out the learning process in finding more detailed and accurate information.